Pengaruh Dimensi Motivasi Kunjungan Terhadap Preferensi Wisatawan Berkunjung ke Objek Wisata Gunung Fatuleu Kabupaten Kupang - Srie Norma Sulisetiawati (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia, 2024)
Tourism activities have now become part of the lifestyle of people in all circles who have the desire to have a recreation in a tourist destination. So it is not surprising when the need for people to travel continues to increase. Mount Fatuleu is one of the tourist attractions in Kupang Regency which is the choice of tourists for traveling. It is undeniable that the number of visits from year to year, Mount Fatuleu Tourism Object is increasing. This study aims to analyze the effect of physical motivation, cultural motivation, personal motivation, status and position motivation on preference from Mount Fatuleu, Kupang Regency. The independent variables (X) in this study are physical motivation (X1), cultural motivation (X2), personal motivation (X3), status and position motivation (X4). Meanwhile, the stress variable in this study is preference (Y). The study population was the tourists of Mount Fatuleu, and the sampling technique used observation and questionnaires. Respondents who met the requirements were determined as many as 97 tourists who were analyzed by SPSS. The results showed that culture, personality, status and position had a simultaneous and partial effect on tourist visit decisions. The results of the descriptive analysis show that the four independent variables have an average score in the positive area.Where the highest average score is personal at 3.31 while the lowest is physical 3.20 while multiple linear regression analysis shows Y = -0.112 + 0.804X1 + 0.666X2 + 0.695X3 + 1.147X4. The coefficient of determination obtained shows 97% preference is influenced by physical, cultural, personal, status and position.